EFFECT OF MEAL SEQUENCING ON GLP-1 HORMONE AND POSTPRANDIAL GLUCOSE EXCURSION IN PRE-DIABETIC PATIENTS: A CROSSOVER TRIAL - Serichantalergs, Nida; Boonyavarakul, Apussanee (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Meal sequencing is a novel approach for improving postprandial GLP-1 and glycemic responses. Previous studies have found that consumption of a fiber-enriched diet, high-protein or high-fat diet before a highcarbohydrate diet increased GLP-1 secretion and lowered postprandial glucose excursion. To determine such responses in Thai pre-diabetic subjects, we performed meal sequencing patterns using common Thai meal viands including “boiled vegetables,” “grilled pork,” and “sticky rice.” METHODOLOGY We conducted a crossover trial with a meal sequence test in 15 prediabetic adults aged 20 years or older. The participants ingested vegetables followed by meat and sticky rice (V-M-R) on day 1, vegetables with meat followed by sticky rice on day 2 (VM-R), and vegetables with meat and sticky rice on day 3 (VMR). GLP-1 levels and plasma glucose levels were measured at 0, 30, 60, and 120 min after ingestion. RESULTS The consumption of vegetables before meat and sticky rice (V-M-R) significantly increased GLP-1 AUC (0-120) than the consumption of vegetables with meat, followed by sticky rice (VM-R) or vegetables with meat and sticky rice (VMR) (V-M-R 5213.4 ± 2114.37 Vs VM-R 3869.02 ± 1362.68 Vs VMR 3426.16 ± 1478.15; p <0.05). Both V-M-R and VM-R induced significantly lower postprandial glucose AUC (0- 30) and AUC (0-60) compared to VMR (At 30 min, V-M-R 3154.79 ± 336.9 Vs VM-R 3161.35 ± 230.17 Vs VMR 3585.87 ± 597.49; At 60 min, V-M-R 6664.83 ± 673.43 Vs VM-R 6594.59 ± 632.58 Vs VMR 7636.53 ± 1056.38, p <0.05). CONCLUSION The V-M-R meal sequence enhanced more GLP-1 release than other meal sequence patterns (VM-R and VMR) and produced less postprandial glucose excursion. The results provide the possibility of meal sequencing as a new nonpharmacological treatment for diabetic prevention in prediabetic patients